Determination of optimum fermentation time through microscopic, sensory, and eating quality comparison of hyacinth beans, sword beans, and soybean tempeh - Jacob, Alexander Michael; Gaby, Cecilia; Rachman, Hans; Sulistyo, Joko; Krisbianto, Oki (AGROINTEK, 2025)
Tempeh is a traditional Indonesian fermented food made from soybeans, which are rich in protein and essential nutrients. However, the increasing demand for soybeans, particularly in Indonesia, has led to a search for alternative legumes. This study aims to evaluate the potential of hyacinth beans (HB) and sword beans (SD) as alternative legumes for tempeh production in comparison to conventional soybean (SB) tempeh. The research was conducted in two phases. The first phase was determining the optimum fermentation duration for HB and SD tempeh compared to SB tempeh using sensory appearance, hardness, and microscopic observation. The second phase was to determine the eating quality of all tempeh, which were steamed and fried, by sensory evaluation supported by color and texture analyses. Protein content analysis was also conducted on raw and cooked tempeh. Results showed that optimal fermentation durations were determined as 36 hours for HB and SD and 48 hours for SB tempeh, which had optimum sensory appearance, hardness, and Rhizopus mycelial growth. SB tempeh was more favored in the second phase than HB and SD tempeh. The preference for SB tempeh compared to the other two was thought to be because the panelists were more familiar with the sensory characteristics of SB tempeh. Protein content was highest in fried SB tempeh (37.49%), significantly increasing due to moisture loss during frying. While the original tempeh made from SB remains the most favored, non-SB legumes, especially SD, also present viable alternatives for tempeh production. Consequently, non-SB tempeh has the potential to reduce dependence on soybeans and support food diversification.